ANALISIS TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III MENJELANG PERSALINAN - Siskha Maya Herlina; Yadul Ulya; Regina Pricilia Yunika (PROFESSIONAL HEALTH JOURNAL, 2023)
Abstract Introduction: Childbirth is a stressful event that causes increased pain, anxiety, fear of damage or body deformities such as episiotomy, rupture, stitches or cesarean section, and the mother is afraid that she will injure her baby. During pregnancy, the mother experiences physical and psychological changes, the effects of anxiety in labor. Purpose: of this study was to determine the level of anxiety in third trimester pregnant women before delivery. This research method used a descriptive survey with data collection stages using a questionnaire which was distributed to all pregnant women during the study period. Methods: In this study the type of research used was a quantitative method with a cross sectional design. Results: most of the third trimester pregnant women who were at the Kasihan II Health Center experienced anxiety as many as 46 respondents 95.83% with each different level of anxiety, namely mild anxiety 30 respondents (53.6%), moderate anxiety 13 respondents (23, 2%), 3 respondents (5.4%) had severe anxiety, and 2 respondents did not experience anxiety. Conclusion: The results show that the higher the level or status of the respondent's characteristics, the lower the level of anxiety that appears, as in the level of severe anxiety, the characteristics that greatly affect severe anxiety are age <20 years, income <1 million, primigravidas and those with primary school education